Systemic inflammation, cellular influx and up-regulation of ovarian VCAM-1 expression in a mouse model of polycystic ovary syndrome (PCOS) - Solano, Maria Emilia (2011)
PCOS, a major cause of anovulatory sterility, is associated with obesity, insulin resistance and chronic inflammation. New evidence suggests that the immune system aggravates the clinical features of PCOS. Our aim was to study the immune, metabolic and endocrine features of a mouse model of PCOS elicited by androgenisation using dehydroepiandrosterone (DHEA). We observed a significant weight gain and insulin resistance in DHEA-androgenised mice, coupled with the formation of ovarian follicular cysts. DHEA up-regulated the expression of vascular cell adhesion molecule (VCAM)-1 and intercellular adhesion molecule (ICAM)-1 in the granulosa cell layer of the majority of cysts, and VCAM-1 expression in the theca cell layer of all follicles and cysts. The expression of these markers was low in control tissue. Peritoneal cells from PCOS-mice showed enhanced production of inflammatory cytokines, suggesting an association between chronic inflammation and PCOS. In addition, DHEA-androgenisation induced the activation of CD4+ cells both in vivo and in vitro, and their expression of the respective ligands for VCAM-1 and ICAM-1, VLA-4 and LFA-1, as assessed in vitro. CD4+ cells were present in androgenised ovaries, especially in the granulosa cell layer of cysts with high VCAM-1 expression. Herein, we present novel evidence that the immune system is activated systemically and locally in a mouse model for PCOS. We propose that VCAM-1 is involved in aggravating PCOS symptoms by promoting leukocyte recruitment to the ovaries and perpetuating local inflammation. These findings offer novel therapeutic opportunities for PCOS, such as blockage of VCAM-1 expression.